Innovations in Business Process Digitalisation in the Forest-Wood Sector In Slovenia (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
Digital technology can help businesses automate and streamline various processes to optimise resource use, improve efficiency, and reduce costs. This paper aims to study digitalisation in Slovenia’s forest-wood sector, which is essential to the country’s smart specialisation strategy. Based on a survey we conducted among 294 enterprises in this sector, we study a subsample of innovators that were asked if they introduced or are planning to introduce innovations in business process digitalisation such as collaboration with IT or data experts, implementation of sensor technologies, digital modelling and simulation, collaborative platforms, and other technologies that can help the sector to improve manufacturing and production processes, logistics and sales. The results show that adopting digital technologies is correlated with enterprise strategy, investments in R&D, collaboration with universities and research institutes, the share of employees with a tertiary degree and in RDI positions, and enterprise size.